Enhancing Commitment to Change The Role of Perceived Supervisor Support and Self Efficacy - Meilina Sungkawaningtyas; Sumaryono Sumaryono; Diah Retno Wulandaru (Green Publisher Indonesia, 2024)
The relationship between perceived supervisor support and self-efficacy with acceptance of change has been commonly studied, but no one has examined the relationship between perceived supervisor support and self-efficacy on commitment to change especially on the implementation of change policies of government organisations in Indonesia. This study presents the findings of an investigation into the moderating role of self-efficacy in the relationship between perceived supervisor support and affective, continuance, and normative commitment to change. This research is specifically necessary within the framework of executing organizational change policies in government organizations in Indonesia. A survey was administered to 255 workers of a public sector organization who were undergoing a reform program. The analysis of structural equation modeling indicated a favourable association between perceived supervisor support and affective and normative commitment to change. Therefore, the connection between how employees view their supervisor's support and their affective and normative commitment to change depends on their belief in their own ability to succeed.